1992
DOI: 10.1002/glia.440050202
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and release of neuroactive substances by glial cells

Abstract: Glia contain, synthesize, or release more than 20 neuroactive compounds including neuropeptides, amino acid transmitters, eicosanoids, steroids, and growth factors. The stimuli that elicit release differ among compounds but include neuropeptides, neurotransmitters, receptor agonists, and elevated external [K+]. The mechanisms of release are poorly understood in most cases. Many of the neuroactive compounds are localized in discrete subpopulations of glia. Thus, glia are equipped to send as well as receive chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
173
0
5

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(182 citation statements)
references
References 104 publications
(144 reference statements)
4
173
0
5
Order By: Relevance
“…However, physiological understanding of neuron-to-glia versus glia-to-neuron communication pathways is still being elucidated. Astrocytes express receptors for neurotransmitters (Verkhratsky and Steinhä user, 2000;Araque et al, 2001), and they produce and release neuroactive substances (Martin, 1992). In addition, stimulation of astrocytes with a variety of neurotransmitters induces an elevation of intracellular calcium, which propagates as calcium waves to neighboring astrocytes via gap junctions (Araque et al, 2001).…”
Section: Neuroprotective and Neuromodulatory Functions Of Egcmentioning
confidence: 99%
“…However, physiological understanding of neuron-to-glia versus glia-to-neuron communication pathways is still being elucidated. Astrocytes express receptors for neurotransmitters (Verkhratsky and Steinhä user, 2000;Araque et al, 2001), and they produce and release neuroactive substances (Martin, 1992). In addition, stimulation of astrocytes with a variety of neurotransmitters induces an elevation of intracellular calcium, which propagates as calcium waves to neighboring astrocytes via gap junctions (Araque et al, 2001).…”
Section: Neuroprotective and Neuromodulatory Functions Of Egcmentioning
confidence: 99%
“…There is now clear evidence that glial cells express a large variety of receptors for neuropeptides, which are functionally coupled to second messenger systems [12,13]. We have recently found that ODN stimulates calcium mobilization in rat astrocytes [14].…”
Section: Introductionmentioning
confidence: 95%
“…Increase in SCBF at the site of SCI correlates with improvement in the function of acutely injured spinal axons, 25,29 and glutamate signaling may play a role in modulation of blood¯ow and blood brain barrier permeability. 30 Therefore, we hypothesize that treatment with an NMDA antagonist after acute SCI would a ect axonal function by blocking NMDA receptors and reducing neurotoxicity at the injury site, and that there would be an increase in blood¯ow and a decrease in edema in the injured spinal cord. 31 ± 33 To test these hypotheses, we observed the e ects of pre-and posttreatment with MK801 on the axonal conduction, posttraumatic ischemia and cord edema by measuring evoked potentials, SCBF and cord water content, respectively, after acute compression SCI in rats.…”
Section: Introductionmentioning
confidence: 99%